X Squared Plus Three X Minus 10 =0

The algebraic expression for the statement is;

x2 + 3x - 10 =0

It is a quadratic equation in x. There are two factors of the given equation. The given equation will give two values of variable x.

x2 + 3x - 10 = 0

x2 + 5x - 2x - 10 = 0

x( x + 5) -2( x + 5) =0

(x - 2)(x + 5) =0

(x - 2) =0 ; (x + 5) =0

x = -5, 2

Sop, the required values of the variable x are -5 and 2.

The algebraic expression for the statement is;

x2 + 3x - 10 =0

It is a quadratic equation in x. There are two factors of the given equation. The given equation will give two values of variable x.

x2 + 3x - 10 = 0

x2 + 5x - 2x - 10 = 0

x( x + 5) -2( x + 5) =0

(x - 2)(x + 5) =0

(x - 2) =0 ; (x + 5) =0

x = -5, 2

Sop, the required values of the variable x are -5 and 2.